PENERAPAN PERMAINAN TAMBANG UNTUK PEMBELAJARAN MATEMATIKA DALAM PENINGKATAN KEMAMPUAN KOGNITIF-MATEMATIS PADA ANAK KELOMPOK A DI TK DIPONEGORO SRIMULYO DAMPIT-MALANG - Siti Khotijeh Kubro; Nikmahtul Khoir Tri Yulia (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2022)
The Mining games aim to develop children's cognitive-mathematical abilities in learning mathematics. The purpose of the research includes to describe the process of learning mathematics in mining games to improve children's cognitive abilities. This type of research uses a case study and the approach uses classroom action research (CAR). Teaching by (Home Visit) visits to students' homes in one week with 3 meetings. Data analysis techniques were obtained from observation data, interview data, and documentation data. The results and discussion of the research include the process of learning mathematics that can use modifications from the use of existing learning media. The average result of the increase between cycles I and II in each meeting (I) was 67.70%. (II) 75.78%, (III) 81.51% through the evaluation of 16 children in group A. The study concluded that mining games in mathematics learning had increased very significantly. The application process that pays attention to aspects of concentration, speed, and accuracy in cognitive-mathematical abilities in early childhood.